Shahid, Alhassan. “The Intellectual Thought of al-Shāṭibī and Ibn Khaldūn: An Epistemological Methodological Approach,” Year 15, Issue 57 (Summer 1430 AH/ 2009 CE), Pp. 83-122. - شهيد الحسان (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2009)
Alhassan Shahid’s article is a comparative study of the writings of Ibn Khaldūn and al-Shāṭibī aimed at understanding their methodological approaches. It examines the facets of methodological similarities in terms of their intellectual approach, discourse, and awareness of the extent of epistemological integration between the uṣūlī and historical discourses. The study finds that al-Shāṭibī and Ibn Khaldūn meet in issues of inductive research and have formed a new discourse whose effects are still evident today. The study is based on a set of primary and secondary principles, including: the foundations of the parallel choice between the two sciences, routes of inductive analysis and its dimensions between the two scholars, how each one became preoccupied by the other, characteristics of inductive analysis, and the analytical comprehensiveness of both al-Shāṭibī and Ibn Khaldūn.